Strategi Komunikasi Kepala Bidang Urusan Agama Islam untuk Meningkatkan Kinerja Pegawai Kantor Wilayah Kementerian Agama Provinsi Sumatera Barat - Vivi Hadyati; Desi Syafriani (STIKes Ibnu Sina Ajibarang, 2024)
Communication strategy is a plan in communicating with the aim of achieving a goal. Communication is basically an activity of exchanging ideas or activities or ideas in conveying ideas and the meaning of messages from one party to another. Activities carried out in an agency are always accompanied by the goals that fellow groups want to achieve. This research focuses on answering how the Communication Strategy of the Head of the Islamic Affairs Division to Improve Employee Performance of the Regional Office of the Ministry of Religion of West Sumatra Province. The type of research used is using descriptive qualitative research methods. The data collection techniques used in this study were observation, interview, and documentation techniques. The data analysis techniques that the authors use in this study are data reduction, data presentation and verification/conclusion. The primary data source in the study is the head of the field of Islamic religious affairs of the regional office of the ministry of religion of West Sumatra province and the secondary data in this study are in the form of archives and documentation in the field of religious affairs and communication of the head of the field of Islamic religious affairs of the regional office of the ministry of religion of West Sumatra province. The results obtained are that the strategy used by the head of the field of Islamic religious affairs to improve the performance of employees of the regional office of the ministry of religion of West Sumatra province is the Hafied Cangara communication strategy, which uses the method of selecting and determining communicators, recognizing targets, assessing the objectives of communication messages, and selecting media.